The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0269215518802886
|View full text |Cite
|
Sign up to set email alerts
|

A structured exercise programme combined with proprioceptive neuromuscular facilitation stretching or static stretching in posttraumatic stiffness of the elbow: a randomized controlled trial

Abstract: Objectives: To compare the different stretching techniques, proprioceptive neuromuscular facilitation (PNF) stretching and static stretching, in patients with elbow stiffness after a treated elbow fracture. Design: Randomized-controlled, single-blind study. Setting: Department of physiotherapy and rehabilitation. Subjects: Forty patients with posttraumatic elbow stiffness (24 women; mean age, 41.34 ± 7.57 years). Intervention: PNF stretching group (n = 20), hold-relax PNF stretching combined with a structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 30 publications
0
9
0
6
Order By: Relevance
“…It is thought that the increase in ROM and the extension of soft tissues affect muscle strength, thus reducing the range of pain. This proved that the HR technique affected VAS and SPADI more than MWM [31,32].…”
Section: Discussionmentioning
confidence: 70%
“…It is thought that the increase in ROM and the extension of soft tissues affect muscle strength, thus reducing the range of pain. This proved that the HR technique affected VAS and SPADI more than MWM [31,32].…”
Section: Discussionmentioning
confidence: 70%
“…Thirty-one studies were included in the final analysis (Beltran-Alacreu et al, 2015 ; Hidalgo et al, 2015 ; Pires et al, 2015 ; Sarig Bahat et al, 2015 ; Castro-Sánchez et al, 2016 ; Pillastrini et al, 2016 ; Cruz-Díaz et al, 2017 ; Martínez-Cervera et al, 2017 ; Yilmaz Yelvar et al, 2017 ; Birinci et al, 2019 ; Gholami et al, 2020 ). The identification process is shown by a flow diagram in Figure 1 (Moher et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although both the methods improved hamstring flexibility, there was no difference in the efficacy of the two methods. However, when Birinci et al [11] randomly allocated PNF and static stretching to patients with elbow stiffness after a treated elbow fracture, they observed improvement in arm pain, ROM, and function particularly in the PNF stretching group. Tucker and Slone [24] applied PNF stretching, PNF stretching combined with vibration, and static stretching to patients with glenohumeral internal rotation deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Jeong and Kim [10] observed that application of PNF stretching significantly reduces low back pain and dysfunction in patients with chronic low back pain. Birinci et al [11] reported significant improvements in elbow pain, range of motion (ROM), and arm function upon the application of PNF stretching in patients with elbow stiffness. Gunn et al [12] reported that PNF stretching is more effective for hamstring flexibility than static stretching.…”
Section: Introductionmentioning
confidence: 99%